Пілотне тепломасообмінне обладнання для комплексної переробки рослинних відходів в біопаливо і побічні продукти - Ободович, Олександр Миколайович; Сидоренко, Віталій Володимирович; Булій, Юрій Володимирович; Азаров, Сергій Павлович (My University, 2022)
В статті представлено пілотне, дослідно-промислове тепломасообмінне обладнання для проведення комплексної переробки рослинних відходів сільськогосподарського виробництва в тверде (лігнін) та рідке (біоетанол) біопаливо і побічні продукти. Описано конструкцію та принцип роботи установки. Представлено результати досліджень по делігніфікації соломи пшеничної на пілотній дослідно-промисловій установці. The most significant source of biomass is wood and agricultural crops. The experience of a number of productions, in particular hydrolysis, allows solving the problem of the profitability of processing organic biomass by means of its deep complex processing with obtaining components, the cost of which exceeds the cost of the original organic raw materials, such as fuel. The main results of the complex processing of organic raw materials are increasingly energy-containing products, namely bioethanol and hydrolyzed lignin, which have energy characteristics comparable to fossil fuels. One of the stages of bioethanol production is the hydrolysis stage, which consists of the pretreatment of raw materials before hydrolysis and direct hydrolysis (acidic or enzymatic).
Keywords: кафедра біотехнології продуктів бродіння і виноробства; біоетанол; попередня підготовка; делігніфікація; луг; ротор; дискретно-імпульсне введення енергії; bioethanol; pretreatment; delignification; alkali; rotor; discrete-pulsed energy input